Collecting and Monitoring for Northern Fowl Mite (Acari: Macronyssidae) and Poultry Red Mite (Acari: Dermanyssidae) in Poultry Systems. Issue 6 (2nd November 2020) - Murillo, Amy C; Mullens, Bradley A
Abstract: The two most economically important poultry ectoparasites are the northern fowl mite, Ornithonyssus sylviarum (Canestrini and Fanzago), and the poultry red mite, Dermanyssus gallinae (De Geer). Both mites are obligate blood feeders but differ in where they reside. Sampling methods thus focus on-host, especially the vent feathers, for northern fowl mite and off-host, especially cracks and crevices near the nighttime roosting areas, for poultry red mite. Much remains unknown, however, about the basic biology and ecology of both mites. Here we discuss mite detection, quantification, and decision making and provide thoughts on future directions for research.